Collision tumor of the palate: A rare case report - Shoaib R Tippu; Farzan Rahman; Neha Sharma; Shalabh Srivastava (Wolters Kluwer Medknow Publications, 2014)
This case report presents an unusual swelling of the palate in a 61-year-old-male patient. Histopathologically, it revealed features of two separate adjacent lesions, a spindle cells lesion showing diffuse immune-positivity for S-100 protein and focal positivity to glial fibrillary acid protein and an osseous lesion with numerous trabaculae of bone, adipocytes and myxoid tissue confirming the diagnosis of collision tumor of benign peripheral nerve sheath tumor and osteoma. Extensive search of English literature shows no reported cases of peripheral nerve sheath tumor with osteoma. The probable histogenesis of this collision tumor is discussed in detail. The purpose of this case report is to document this rare case in the literature so as to increase the awareness of this entity.